2018
DOI: 10.18203/2320-1770.ijrcog20184475
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile and cardiovascular risk indices of women on various types of contraceptives in the Ho Municipality of Ghana

Abstract: Background: Hormonal contraceptives (HCs) have been successfully used worldwide to prevent pregnancy by inhibiting ovulation and implantation. These contraceptives have effects on lipid metabolism, body fat and blood pressure which are all risk factors for cardio vascular disease (CVD). Some studies have reported that prolonged use of these hormone-based contraceptives have negative effect on cardiovascular risk indices, however, few of such studies have been done in Ghana, hence this study sought to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
4
5
2
Order By: Relevance
“…The finding is consistent with that of a study by Bawah et al . [ 28 ], while it is not consistent with findings from a study in Ghana [ 21 ]. The studies found a significant difference in DBP and an insignificant difference in SBP among DMPA users and non-users.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…The finding is consistent with that of a study by Bawah et al . [ 28 ], while it is not consistent with findings from a study in Ghana [ 21 ]. The studies found a significant difference in DBP and an insignificant difference in SBP among DMPA users and non-users.…”
Section: Discussioncontrasting
confidence: 79%
“…[ 21 ] which revealed that DMPA users have a significantly higher BMI than non-users. An animal study by Bakery and Abdullah also revealed that DMPA-treated rats have significantly increased weight gain than those not treated [ 27 ], although this is not consistent with the finding by Bawah et al that showed statistically insignificant difference in body weight between DMPA users and non-users [ 28 ]. DMPA-associated weight gain may be due to its effects on the regulation of appetite and energy expenditure by reducing cerebrospinal fluid leptin levels or its glucocorticoid-like activity [ 37 ].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations